2012
DOI: 10.1021/jm201570s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Assessment of Globotriose–Chitosan Conjugate, a Novel Inhibitor of Shiga Toxins Produced by Escherichia coli

Abstract: Shiga toxin (Stx)-producing Escherichia coli (STEC) causes diarrhea and colitis in humans that can develop into a life-threatening hemolytic uremic syndrome (HUS). Developing efficient means of controlling STEC diseases, for which no drugs or vaccines are currently available, remains a high priority. We report here the construction and development of chitosan conjugates bearing the Stx ligand trisaccharide globotriose to demonstrate their potential as STEC disease treatment agents. The synthesis was accomplish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 64 publications
(127 reference statements)
0
15
0
Order By: Relevance
“…These cell-permeative peptides were also protective in a baboon model following Stx2 injection, as renal injury was abated (386). Cytotoxicity of both Stx1 and Stx2 could be neutralized with globotriose conjugated to the polysaccharide chitosan, by binding the toxin (387). This globotriose conjugate was also able to protect mice against STEC O157:H7 challenge.…”
Section: Clinical Considerationsmentioning
confidence: 96%
“…These cell-permeative peptides were also protective in a baboon model following Stx2 injection, as renal injury was abated (386). Cytotoxicity of both Stx1 and Stx2 could be neutralized with globotriose conjugated to the polysaccharide chitosan, by binding the toxin (387). This globotriose conjugate was also able to protect mice against STEC O157:H7 challenge.…”
Section: Clinical Considerationsmentioning
confidence: 96%
“…49 Table 2 shows some of the examples of chitosan conjugates. Chitosan-doxorubicin Conjugate prepared via succinate linker.…”
Section: Chitosan Based Conjugatesmentioning
confidence: 99%
“…The strong neutralization effect observed with SUPER TWIG and the Gb3 polymers is due to the fact that the B pentamer of the Stxs contains multiple Gb3-binding sites, so receptor mimics that display multiple copies of the Gb3 trisaccharide bind the toxin tightly. A similar approach as described above was used by another group to display the receptor sugar moiety on chitosan, and they similarly found that the analog neutralizes in vitro and in vivo (48).…”
Section: Receptor Analogsmentioning
confidence: 88%